Concept “Legally Constituted Court” of National and International Law (Definition Problem) - Inna Anatolyevna Orlova (Управленческое консультирование)
The article analyzes the interpretation of the category «out established by law» in national and international law, as well as in the practice of international law enforcement agencies. The doctrinal views on the category of «legality» in the international law are examined. The criteria for the legitimacy of creating one of the types of international jurisdictional bodies - international courts, as well as national courts «with elements of internationality» - «hybrid ships» are studied.